Analytical investigation on bond behavior between concrete and FRP bars of near-surface mounted and embedded through-section strengthening methods - Kongmalai, Nakares; Van Hong Bui, Linh; Jongvivatsakul, Pitcha (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 25, 2020)
The strengthening techniques are to enhance the performance of existing reinforced concrete (RC) structures. This research aims to investigate the bond behavior between fiber-reinforced polymer (FRP) bars and concrete interfaces of near-surface mounted (NSM) strengthening method and the embedded through-section (ETS) strengthening technique. Bond models for two strengthening methods are developed considering various crucial parameters. The effects of concrete compressive strength, embedment length, and modulus of elasticity of FRP bars on the bond responses between two retrofitting methods are analytically investigated to interpret the results through bond models.